Legal Certainty of Business use Rights Certificate (SHPTU) as Credit Collateral Due to Default - Widjaja, Wilson Hartanto; Kan, James (CV. Publikasi Indonesia, 2025)
SHPTU, credit collateral, default, fiduciary, cessie, legal certainty This study examines the legal certainty surrounding the use of the Business Use Rights Certificate (SHPTU) as credit collateral in cases of default. Although the Regional Regulation of DKI Jakarta Province Number 7 of 2018 states that SHPTU can be used as collateral, it does not explicitly define whether SHPTU constitutes a property right or a personal right. Using a normative-empirical legal research method, this study is based on primary data from interviews and secondary data from legislation and legal literature. The findings indicate that SHPTU closely resembles a leasehold right rather than ownership, and therefore, cannot be used as a collateral object under material security mechanisms such as fiduciary or mortgage. In the event of default, SHPTU cannot be executed directly. The resolution must involve mediation and assignment of receivables (cessie) through a power of attorney agreement. This study recommends the need for clearer regulation to ensure legal certainty and protection for creditors.